Anti-cancer and anti-inflammatory effects elicited by short chain fatty acids produced by Escherichia coli isolated from healthy human gut microbiota - Nakkarach, Atchareeya; Foo, Hooi Ling; Song, Adelene Ai-Lian; Mutalib, Nur Elina Abdul; Nitisinprasert, Sunee; Withayagiat, Ulaiwan (Microbial cell factories, 2021)
Extracellular metabolites of short chain fatty acids (SCFA) excreted by gut microbiota have been reported to play an important role in the regulation of intestinal homeostasis. Apart from supplying energy, SCFA also elicit immune stimulation in animal and human cells. Therefore, an attempt was conducted to isolate SCFA producing bacteria from healthy human microbiota. The anti-cancer and anti-inflammatory effects of extracellular metabolites and individual SFCA were further investigated by using breast, colon cancer and macrophage cells. Toxin, inflammatory and anti-inflammatory cytokine gene expressions were investigated by RT-qPCR analyses in this study. Escherichia coli KUB-36 was selected in this study since it has the capability to produce seven SCFA extracellularly. It produced acetic acid as the main SCFA. It is a non-exotoxin producer and hence, it is a safe gut microbiota. The IC values indicated that the E. coli KUB-36 metabolites treatment elicited more potent cytotoxicity effect on MCF7 breast cancer cell as compared to colon cancer and leukemia cancer cells but exhibited little cytotoxic effects on normal breast cell. Furthermore, E. coli KUB-36 metabolites and individual SCFA could affect inflammatory responses in lipopolysaccharide-induced THP-1 macrophage cells since they suppressed inflammatory cytokines IL-1β, IL-6, IL-8 and TNF-α well as compared to the control, whilst inducing anti-inflammatory cytokine IL-10 expression. SCFA producing E. coli KUB-36 possessed vast potential as a beneficial gut microbe since it is a non-exotoxin producer that exhibited beneficial cytotoxic effects on cancer cells and elicited anti-inflammatory activity simultaneously. However, the probiotic characteristic of E. coli KUB-36 should be further elucidated using in vivo animal models.